2004
DOI: 10.1016/j.resconrec.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The optimisation of household waste recycling centres for increased recycling—a case study in Sussex, UK

Abstract: Sixteen percent of household waste in the UK is handled at Household Waste Recycling Centres (HWRC). These facilities will play an important role if the UK is to achieve the national target of recycling 25% of household waste by 2005, as most sites now provide containers for recyclables as well as a mixed waste pile. However, few published studies have been conducted regarding the activities of HWRC site users and the composition of waste that is delivered, especially to the mixed waste pile. This paper presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 1 publication
1
25
0
1
Order By: Relevance
“…The results from this study regarding user characteristics, type of vehicle used, travel distances, number of stops, number of visited fractions, and amounts of wrongly sorted waste are in reasonable agreement with other studies from Civic Amenity sites or other Household Waste Recycling Centres (Williams and Taylor, 2004;Woodard et al, 2004;Belton et al, 1994). Most users did not experience difficulties with the distance they had to travel to the recycling centre.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results from this study regarding user characteristics, type of vehicle used, travel distances, number of stops, number of visited fractions, and amounts of wrongly sorted waste are in reasonable agreement with other studies from Civic Amenity sites or other Household Waste Recycling Centres (Williams and Taylor, 2004;Woodard et al, 2004;Belton et al, 1994). Most users did not experience difficulties with the distance they had to travel to the recycling centre.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have identified that a considerable amount of certain types of products discarded are potentially re-usable (Woodard et al, 2004). However, the present recycling centre concept does not support reuse of products well.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A facility where the area is too confined leads to traffic problems and unnecessary irritation, also found by (Woodard et al, 2004). An efficient flow of visitors is good both for the visitors and the employees.…”
Section: Discussionmentioning
confidence: 85%
“…In Wilkes Barre, Pennsylvania, it resulted in a saving of US$500,000 in landWlling avoidance costs during the period between 1988 and 1991 (Agunwamba et al, 1998). In England household waste recycling centers handle 16% of household waste (Woodard et al, 2004).…”
Section: Introductionmentioning
confidence: 99%